2017
DOI: 10.1177/0739456x16685157
|View full text |Cite
|
Sign up to set email alerts
|

Decent Work and Social Protection in Belo Horizonte, Brazil

Abstract: This paper examines how beneficiaries of Brazil's Bolsa Família (BFP) conditional cash transfer program find employment in a Brazilian municipality, and assesses their participation in decent work. Using Belo Horizonte as a case study, researchers conducted a survey of BFP recipients. The paper compares responses of informally and formally employed workers to assess how their employment meets the criteria of the decent work agenda. Results indicate no significant difference between perceptions of formal and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The results from the 77 participant observations in the first group of questions revealed that the main workers in the area were kiosk sellers (58 observations), vendors (33), traffic officers (31), sellers of ready-to-eat food (27), site construction workers (26), mechanics (27), and street workers (11). Forty-three observers found the workers neither satisfied nor dissatisfied, and 19 reported that the workers were dissatisfied.…”
Section: Results From Participant Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The results from the 77 participant observations in the first group of questions revealed that the main workers in the area were kiosk sellers (58 observations), vendors (33), traffic officers (31), sellers of ready-to-eat food (27), site construction workers (26), mechanics (27), and street workers (11). Forty-three observers found the workers neither satisfied nor dissatisfied, and 19 reported that the workers were dissatisfied.…”
Section: Results From Participant Observationsmentioning
confidence: 99%
“…Thus, this study goes some way toward filling the gap in the literature on the contextual design factors for workers in public spaces. Although previous studies have identified several factors that affect worker productivity and the provision of a decent work environment [11], additional studies are needed to understand more completely the key tenets of the effects of the built environment on decent work conditions.…”
Section: Interpreting the Collected Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ILO defines expanding social protection as "enhancing both involvement and performance by securing both women and men's chances to experience a safe working environment, offer appropriate leisure time, offer sufficient support in the case of decreased or complete loss of wages, and provide health insurance benefits; moreover, the family members of workers should benefit from social protection as well". Social protection is believed to play a key role in alleviating poverty, protecting children's rights and tackling different kinds of inequalities (Haddad and Hellyer, 2018). Floro and Meurs (2009) highlighted that, compared with men, women are relatively more affected by social protection programmes, which could be because women generally carry the heavier burden of childcare and other family duties.…”
Section: Social Protectionmentioning
confidence: 99%
“…Many countries provided 18 weeks of maternity leave, but the majority of countries in Asia, Africa and Latin America, in addition to the USA, provided female workers with less than 14 weeks off work. Haddad and Hellyer (2018) reported that workers in some specific sectors (e.g. construction and domestic workers) are deprived of social protection, which could significantly impact women because they can end up having no lawful rights to maternity leave.…”
Section: Social Protectionmentioning
confidence: 99%